Determinants of Bilateral Trade Balance Between Georgia and China - Dilanchiev, Azer; Taktakishvili, Tengiz (Ekonomika, 2022)
This paper aims to empirically examine the drivers of the bilateral balance of the trade model for the Georgian-Chinese economy from 2000 to 2020 and the influence of the Georgia-China free trade agreement on the Georgian-Chinese balance of trade. The Error Correction Model (ECM) of the ARDL was used to see if the balance of trade and its predictors have a long-term relationship. One of the ARDL’s defining properties is that it may be utilized in circumstances when there is minimal data, regardless of the level of variable integration. According to the findings, a perceived effective exchange rate has a statistically significant positive impact on the balance of trade in the long run and a statistically significant negative impact on the balance of trade in the short run. The output is shaped to favor the presence of the elasticity attitude’s J-Curve impact. The study also found that the comparative supply of money (MS) and GDP have only a minor impact on the trade balance in the medium and long run. The sponging and monetary methods are ineffective in characterizing the bilateral trade deficit between Georgia and China.